Upaya Meningkatkan Hasil Belajar Siswa Kelas V melalui Penerapan Experiental Learning pada Mata Pelajaran IPAS - Maya Arum Prastiti; Vivi Rulviana; Aning Triastuti (PT PUSTAKA CENDEKIA GROUP, 2025)
This research aims to improve the learning outcomes of class V students in science subjects by applying the Experiential Learning method on food chain material. The method used in the research is Classroom Action Research (PTK) with an Experiential Learning learning design. The research respondents were 12 class V students at SDN Uteran 01 with research instruments in the form of observation sheets to measure student learning outcomes. The research procedure consists of pre-cycle, cycle one and cycle two stages. At the pre-cycle stage, an initial evaluation is carried out in the form of a pre-test to measure student understanding before implementing the Experiential Learning approach. Furthermore, in cycles one and two, an evaluation was carried out in the form of a post test to measure the extent of students' level of understanding after following learning using the Experiential Learning approach. The results showed that at the pre-cycle stage there were 2 students (17%) who achieved a completeness score, this increased in cycle one to 8 students (67%) and again there was an increase in cycle two, namely reaching 10 students (83%) with a score completeness meets the criteria. So it is concluded that the application of Experiential Learning in learning food chains in science subjects significantly improves student learning outcomes.